Wnt/β‐catenin and sonic hedgehog pathways interact in the regulation of the development of the dorsal mesenchymal protrusion. Issue 2 (29th December 2015) - Briggs, Laura E.; Burns, Tara A.; Lockhart, Marie M.; Phelps, Aimee L.; Van den Hoff, Maurice J.B.; Wessels, Andy
Abstract : Background: The dorsal mesenchymal protrusion (DMP) is a second heart field (SHF) derived tissue involved in cardiac septation. Molecular mechanisms controlling SHF/DMP development include the Bone Morphogenetic Protein and Wnt/β‐catenin signaling pathways. Reduced expression of components in these pathways leads to inhibition of proliferation of the SHF/DMP precursor population and failure of the DMP to develop. While the Sonic Hedgehog (Shh) pathway has also been demonstrated to be critically important for SHF/DMP development and atrioventricular septation, its role in the regulation of SHF proliferation is contentious.Results: Tissue‐specific deletion of the Shh receptor Smoothened from the SHF resulted in compromised DMP formation and atrioventricular septal defects (AVSDs). Immunohistochemical analysis at critical stages of DMP development showed significant proliferation defect as well as reduction in levels of the Wnt/β‐catenin pathway‐intermediates β‐catenin, Lef1, and Axin2. To determine whether the defects seen in the conditional Smoothened knock‐out mouse could be attributed to reduced Wnt/β‐catenin signaling, LiCl, a pharmacological activator of this Wnt/β‐catenin pathway, was administered. This resulted in restoration of proliferation and partial rescue of the AVSD phenotype.Conclusions: The data presented suggest that the Wnt/β‐catenin pathway interact with the Shh pathway in the regulation of SHF/DMP‐precursor proliferation and, hence, the development of the DMP. Developmental Dynamics 245:103–113, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: Second Heart Field (SHF)-specific deletion of Smoothened results in reduction of proliferation in the posterior SHF, compromised DMP development, and atrioventricular septal defects. Second Heart Field (SHF)-specific deletion of Smoothened also leads to reduction of expression of Wnt/β-catenin pathway-intermediates. Treatment of mice carrying conditional Smoothened knock-out embryos with LiCl, an activator of the Wnt/β-catenin pathway, results in restoration of SHF proliferation and partial rescue of the AVSD phenotype.